Preservasi arsip digital sebagai upaya penyelamatan informasi di era cloud computing - Nuri Ifka Bengi. MS (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2021)
The rapid development of information technology today has contributed to the birth of archives into new media called digital archives. Digital archives are archives that are stored in digital format to be freely accessible for a long period of time. Archival institutions have an important role in maintaining, storing and preserving archives that have important value in them. To maintain the integrity of the information and ensure that the value of the information contained in the archive can be maintained and used for a long time, the preservation of digital archives needs to be done regularly. The method used in writing this article is the literature study method. This article aims to provide knowledge to readers, namely the wider community and related institutions regarding the necessity of preserving and preserving archives in digital format, namely as an effort and also an alternative in saving important information contained in these archives. Digital preservation, the driving factor must be digital archive preservation as well as some understanding related to digital archive preservation.